Mother's Efforts as a Single Parent in Overcoming Juvenile Delinquency Due to Broken Home in RW 03 Semanggi, East Ciputat - Nisabila, Reizka (Green Publisher Indonesia, 2025)
Divorce often leads to broken home families, which affects the psychological and social development of adolescents. Teenagers from incomplete families are more vulnerable to deviant behaviors. This phenomenon is also found in RW 03 Semanggi, Ciputat Timur, where several adolescents are involved in delinquency such as truancy and smoking. This study aims to analyze the efforts of mothers as single parents in addressing juvenile delinquency caused by broken homes and the challenges they face. The research employed a qualitative method with a case study approach through in-depth interviews. The results show that single mothers strive to improve communication, provide motivation and religious guidance, balance work with child supervision, and collaborate with the community. The main challenges include economic limitations, lack of time, psychological pressure, and minimal social support. This study highlights the crucial role of single mothers and the importance of community support in preventing and reducing juvenile delinquency in broken home families.